Boron and liquid biofertilizer modulate anthocyanin, flavonoid, and protein accumulation in black soybean (Glycine max (L.) Merr.) - Nunun Barunawati; Mochammad Roviq; Salvia Salsabila; Andi Kurniawan (Agrovigor, 2026)
Black soybean (Glycine max (L.) Merr.) is an important source of bioactive compounds, particularly anthocyanins and flavonoids, which contribute to seed nutritional quality. This study evaluated the effects of boron (B) and liquid biofertilizer (LBF) application on flavonoid, anthocyanin, and total protein contents in black soybean seeds. The experiment was conducted in Batu, East Java, Indonesia (739 m above sea level) from May to October 2025 using a randomized block design with three replications. Six treatment combinations were applied: B 2.5 kg ha⁻¹ + LBF 10 mL L⁻¹ (P1), B 2.5 kg ha⁻¹ + LBF 15 mL L⁻¹ (P2), B 5 kg ha⁻¹ + LBF 10 mL L⁻¹ (P3), B 5 kg ha⁻¹ + LBF 15 mL L⁻¹ (P4), B 7.5 kg ha⁻¹ + LBF 10 mL L⁻¹ (P5), and B 7.5 kg ha⁻¹ + LBF 15 mL L⁻¹ (P6). The combination treatment significantly affected flavonoid, anthocyanin, and protein contents. The highest flavonoid and anthocyanin contents were obtained under P5, whereas the highest protein content was recorded under P6. These findings indicate that boron and liquid biofertilizer application can influence the biochemical composition of black soybean seeds, with different treatment combinations favoring the accumulation of secondary metabolites and protein.